Developing functional adaptation in terms of physical competence of some tennis skillsDeveloping functional adaptation in terms of physical competence of some tennis skills - alzahah, Muhanad Karim eabd; Yasser, Imad Kadem (International Journal of Psychosocial Rehabilitation, 2020)
The tests are one of the most important sciences because they are closely related to the amount of results that they seek through the field application to know the scientific truth and through the results, prediction is the goal that the researcher wanted to know the amount of adaptation through some physical abilities and efficiency and some tennis skills, and the researcher concluded to obtain equations to predict from The studied variables are of clear scientific significance, consistent with the nature of the approved components.